Research on the application and training of water combat techniques for security guards - Sun, Haiming; Ding, Yang (Cambridge Sport Science, 2026)
Water security is an important component of security guard work. Compared with other professional skills, research on water security in China has been limited, remaining primarily in the areas of surface swimming protection and first aid, with few studies on water combat techniques. This paper discusses the influencing factors of water combat for security guards, the selection of tactics, techniques, and equipment for water combat, the categories and essentials of water combat, training content for water combat, and training preparation and precautions for water combat.